[Sb4Au4Sb4]2−: A designer all-metal aromatic sandwich - Tian, Wen-Juan; Guo, Jin-Chang; Li, Da-Zhi; You, Xue-Rui; Wang, Ying-Jin; Sun, Zhong-Ming; Zhai, Hua-Jin (The Journal of chemical physics, 2016)
We report on the computational design of an all-metal aromatic sandwich, [Sb4Au4Sb4]2−. The triple-layered, square-prismatic sandwich complex is the global minimum of the system from Coalescence Kick and Minima Hopping structural searches. Following a standard, qualitative chemical bonding analysis via canonical molecular orbitals, the sandwich complex can be formally described as [Sb4]+[Au4]4−[Sb4]+, showing ionic bonding characters with electron transfers in between the Sb4/Au4/Sb4 layers. For an in-depth understanding of the system, one needs to go beyond the above picture. Significant Sb → Au donation and Sb ← Au back-donation occur, redistributing electrons from the Sb4/Au4/Sb4 layers to the interlayer Sb–Au–Sb edges, which effectively lead to four Sb–Au–Sb three-center two-electron bonds. The complex is a system with 30 valence electrons, excluding the Sb 5s and Au 5d lone-pairs. The two [Sb4]+ ligands constitute an unusual three-fold (π and σ) aromatic system with all 22 electrons being delocalized. An energy gap of ∼1.6 eV is predicted for this all-metal sandwich. The complex is a rare example for rational design of cluster compounds and invites forth-coming synthetic efforts.